The resolution of inter-state disputes in civil aviation - Zhang, Luping (Oxford : Oxford University Press, 2022)
In this text, Dr Luping Zhang investigates dispute resolution mechanisms in international civil aviation with a primary focus on the functions of the International Civil Aviation Organization (ICAO) Council.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on January 18, 2022).
Keywords: International Civil Aviation Organization; Aeronautics, Commercial -- International cooperation; Aeronautics, Commercial -- Law and legislation; Dispute resolution (Law)